G602(P) Physical chastisement: Does it still happen?. (27th April 2016) - Middleton, A; DeSoysa, R
Abstract : Aims: Physical chastisement is any punishment in which physical force is used to cause pain or discomfort. Perceptions differ between cultures as to what constitutes acceptable chastisement. Studies have been carried out into physical chastisement in specific ethnic groups but there is a lack of evidence in the United Kingdom (UK) population as a whole. In order to provide meaningful preventative intervention, it is necessary to ascertain the scale and nature of the issue. The aim of this study is to determine the demographics of this problem in one region of the UK. Method: Cases of non-accidental injury referred to a tertiary safeguarding unit between Jan 2014 and Sept 2015 were identified using the electronic database. A retrospective casenote review identified cases of physical chastisement – defined as any physical act carried out as a remedial measure, in a controlled manner, in response to behaviour of a child that was deemed unacceptable by the perpetrator who is a person with authority over the child. We included reflex chastisement. Data were analysed for nature of abuse, perpetrator and cohort demographics. Results: 579 case notes were reviewed with 53/579 (9.2%) fitting our criteria for physical chastisement. 38/53 (72%) of the cases occurred in ethnic minority or immigrant families. The male:female ratio was 1.9:1. The age range was 2–15 years, the majority of cases being 5–10 years old. In 36/53 (68%) of the cases the child was hit with an implement, 33/36 (92%) of these cases involved ethnic minority families. In all cases, the abuser was a primary care giver: 26/53 (49%) mother or step-mother, 22/53 (42%) father or step-father and 5/53 (9.4%) both. Conclusion: Unacceptable chastisement is a complex, emotive and sensitive area of safeguarding work. The negative effects on the child are well documented. The findings of our study reveal that it represents a sizeable proportion of the safeguarding workload and is more likely to occur within some ethnic minority groups. In order to further understand this problem, we must work collaboratively with social care, police, health, education and communities. Any preventative work undertaken to address this issue will need to transcend boundaries – not only between agencies but between cultures.